2016
DOI: 10.4236/abb.2016.72008
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Some Essential Oils Frequently Used in Aromatherapy

Abstract: Genotoxic properties of the essential oils extracted from Artemisia dracunculus (tarragon), Ocimum basilicum (basil), Cinnamomum loureirii (cinnamon), Laurus nobilis (laurel), Satureja montana (savory) and Rosmarinus officinallis (rosemary) are studied by Drosophila melanogaster Somatic Mutation and Recombination Test (SMART). The high bioactivation crossed with a high cytochrome P450-dependent bioactivation capacity is used. This assay is principally based on the loss of heterozygosity of the suitable recessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Nausea can cause disruption of daily activities, such conditions bring pregnant women to unpleasant situations. Seeing the effects of nausea can be said that nausea is one of the problems in the life of pregnant women who forced them to use various ways to prevent the occurrence of nausea in pregnancy (16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Nausea can cause disruption of daily activities, such conditions bring pregnant women to unpleasant situations. Seeing the effects of nausea can be said that nausea is one of the problems in the life of pregnant women who forced them to use various ways to prevent the occurrence of nausea in pregnancy (16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the in vivo antioxidant evaluation, the Wistar rats' liver and kidney samples were used for determining the selected YY and CCP EOs' antigenotoxic activities by means of the comet assay (Tables 6-8) [128,165]. While, to the best of the authors' knowledge, no genotoxicity and/or antigenotoxicity study has been reported for YY EO, the CCP EO isolated from the bark of Cinnamomum burmanii was already assessed using doxorubicininduced Chinese Hamster Ovary (CHO-K1) cells using micronucleus assay [166], Ames Salmonella reversion assay, Bacillus subtilis DNA-repair test (Rec-assay), Escherichia coli WP2uvrA reversion test [167], and Drosophila melanogaster Somatic Mutation and Recombination Test [168]. Herein, the antigenotoxicity of EOs was evaluated against the rCCl 3 OO • that could cause the formation of rMDA and transform the DNA into the aberrant adducts, like M 1 G, M 1 A, and M 1 C (Scheme 2, purple pathway, bold arrows, 28, 29 and 30), which root the transversions and transitions of bases and, upon the quantitative ring-opening, ultimately form N 2 -oxopropenyl-dG, N 2 -oxopropenyl-dA, and N 2 -oxopropenyl-dC adducts (Scheme 2, purple pathway, bold arrows, 31, 32 and 33), leading to the DNA-DNA interstrand cross-links or DNA-protein inter-strand crosslinks [169] to which the comet assay is sensitive [128,165].…”
Section: Eos Antigenotoxic Activity In Vivomentioning
confidence: 99%